Price forecasting of mustard using ARIMA and EGARCH models - Priyanka Solanki; Rajesh Sharma; Madhu Sharma (Journal of Oilseed Brassica, 2026)
Autoregressive Integrated Moving Average (ARIMA) and Exponential GARCH (EGARCH) model wasstudied along with their estimation procedures for modelling and forecasting of mustard price. For forecastingmustard price ARIMA (0,1,1) model is used which gives reasonable and acceptable forecasts but the studyhas revealed that the AR(1)-EGARCH(1,1) model outperformed the price forecasting models for mustardprices primarily due to its ability to capture asymmetric volatility pattern.